Effects of Postpartum Fatigue and Depressive Cognitions on Life Satisfaction and Quality of Life in Arab Postpartum Women: The Intervening Role of Resourcefulness - Hanan A. Badr; Jaclene A. Zauszniewski; Mary Quinn Griffin; Christopher J. Burant; Amy Przeworski; Wedad M. Almutairi; Fatmah H. Alsharif (Nursing Reports, 2021)
The purpose of this study is to explore the relationships among postpartum fatigue (PPF), depressive cognitions, resourcefulness, quality of life, and life satisfaction in Arab postpartum mothers. A conceptual framework is used in this study based on the middle range theory of resourcefulness, which Zauszniewski developed in 2006. The study is a cross-sectional descriptive design with 123 postpartum women who had given birth within the past six months. used WhatsApp and Facebook for recruitment. developed the self-administered online survey in Qualtrics and collected data from 6 January 2017, to 6 February 2017. Correlation analysis is used to address the research aim and used the P value of 0.05 to determine the significance of the results. There were significant correlations among depressive cognitions and resourcefulness, life satisfaction, and quality of life; there were also significant correlations between PPF and life satisfaction, as well as among resourcefulness, quality of life, and life satisfaction. The results of this study emphasized the importance of assessing depressive symptoms and PPF in mothers early in the postpartum period. The results may contribute to designing future intervention studies aimed toward decreasing the risk of mothers with PPF developing more serious depressive symptoms.